Revascularization of the hand, after severe fist wounds with section of its vascular axes - Nusspaumer, Federico; Vivas, Eudoxio; Lizaso, Isabel; Matteucci, Pablo (Cirugía del Uruguay, 1975)
Two casse of revascularization of the hand, after severe wounds in the soft parts of the anterior face of the wrist, with lesions of nerves, tendons and complete section of radial and ulnar vascular pedicles, are reported. In both cases there was evidence of severe distal ischemia. Repair of the two arterial ax.4s was effected by direct suture, as well as primary repair of nerves and the profundus flexor tendons affected. The postoperative course was very good. In the case of this type of lesions it is recommendet that primary integral emergency treatment be applied to ali the structures affected. Prompt physiotherapy is essential to obtain good functional results.